2005
DOI: 10.1152/jn.01168.2004
|View full text |Cite
|
Sign up to set email alerts
|

Testing Bayesian Models of Human Coincidence Timing

Abstract: . A sensorimotor control task often requires an accurate estimation of the timing of the arrival of an external target (e.g., when hitting a pitched ball). Conventional studies of human timing processes have ignored the stochastic features of target timing: e.g., the speed of the pitched ball is not generally constant, but is variable. Interestingly, based on Bayesian theory, it has been recently shown that the human sensorimotor system achieves the optimal estimation by integrating sensory information with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

33
133
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(166 citation statements)
references
References 33 publications
33
133
0
Order By: Relevance
“…The fact that stimulus history biases perceptual judgments is well-known. Broadly speaking, it appears in two ways-biases to (or away from) the mean of a stimulus distribution (1)(2)(3)(4)(5)(6)(7)(8)(9), referred to as central-tendency biases, and biases to (or away from) recently observed stimuli (10)(11)(12)(13)(14)(15)(16), referred to as n − 1 biases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that stimulus history biases perceptual judgments is well-known. Broadly speaking, it appears in two ways-biases to (or away from) the mean of a stimulus distribution (1)(2)(3)(4)(5)(6)(7)(8)(9), referred to as central-tendency biases, and biases to (or away from) recently observed stimuli (10)(11)(12)(13)(14)(15)(16), referred to as n − 1 biases.…”
mentioning
confidence: 99%
“…It has been proposed that central-tendency biases reflect the behavior of a perceptual system that optimally integrates noisy sensory measurements with prior knowledge of the distribution of stimulus values to make perceptual judgments (2,4,(7)(8)(9). Evidence for this hypothesis comes from studies showing that centraltendency biases in perceptual judgments increase when the sensory uncertainty of a stimulus increases (4) or the variance of a stimulus set decreases (2,(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, psychophysical studies have revealed that our brain implements Bayesian integration in a variety of sensory-motor tasks, including spatial reaching 1,5) , reproducing forces 6) , timing 7,8) , and somatosensory temporal order judgment (TOJ) 9,10) (also see Yamamoto et al 2012 11) ). In this article, we first introduce a report that studied the coincidence timing task 8) .…”
Section: Bayesian Integration In Motor Timing Controlmentioning
confidence: 99%
“…In this article, we first introduce a report that studied the coincidence timing task 8) . In this task, the timing component of ball hitting or catching behaviors by humans was extracted.…”
Section: Bayesian Integration In Motor Timing Controlmentioning
confidence: 99%